APACHE II score is superior to SOFA, CTP and MELD in predicting the short‐term mortality in patients with acute‐on‐chronic liver failure (ACLF). Issue 9 (12th August 2013) - Duseja, Ajay; Choudhary, Narendra S; Gupta, Sachin; Dhiman, Radha Krishan; Chawla, Yogesh
<x xml:space="preserve">Abstract</x> Objective The aim of the study was to assess the performance of various prognostic scores including the acute physiology and chronic health evaluation (APACHE II), sequential organ failure assessment (SOFA), Child–Turcotte–Pugh (CTP) and model for end‐stage liver disease (MELD) scores in predicting short‐term mortality in patients with acute‐on‐chronic liver failure (ACLF). Methods Altogether 100 consecutive patients with ACLF were evaluated prospectively. The diagnosis of ACLF was based on the Asian–Pacific Association for the Study of the Liver criteria except for the inclusion of non‐hepatic insults as acute events. Sensitivity, specificity, positive and negative predictive values, and diagnostic accuracy for predicting short‐term mortality was calculated for APACHE II, SOFA, CTP and MELD in all patients and Maddrey's discriminant function (DF) and Glasgow alcoholic hepatitis scores (GAHS) for patients with alcoholic hepatitis only. Results Most patients had alcohol‐related cirrhosis and alcoholic hepatitis as acute insults for ACLF. A total of 53 patients either died or left hospital in very sick status and were confirmed to have died the same day after leaving hospital. Overall, the area under the receiver operating characteristic curve of APACHE II was higher than those of MELD, SOFA and CTP scores for predicting short‐term mortality. Even for patients with alcoholic hepatitis, APACHE II performed better than DF and GAHS. Conclusions Short‐term mortality is high in patients with ACLF. APACHE II scoring system is superior to other prognostic scores in predicting its short‐term mortality.